2018
DOI: 10.1177/2167702617750150
|View full text |Cite
|
Sign up to set email alerts
|

General Factors of Psychopathology, Personality, and Personality Disorder: Across Domain Comparisons

Abstract: Three separate and distinct literatures exist investigating general factors of psychopathology ( factor), personality (GFP), and personality disorder (-PD). Surprisingly, there has been little-to-no investigation regarding the convergence of these three distinct general factors. In the present investigation, two studies were conducted examining the convergence of the factor, GFP, and-PD. In Study 1, a combined model extracting all three factors from self-report data simultaneously found high convergence. The f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
133
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 112 publications
(149 citation statements)
references
References 27 publications
14
133
1
Order By: Relevance
“…More research is needed into the validity of the specific PDs listed in the AMPD, incorporating the specific impairment criteria [88••] and using mixture modeling to test whether they indeed represent latent categories [312]. Finally, future research should continue pursuing a comprehensive conceptualization of mental disorders that integrates major dimensions of personality and psychopathology [313][314][315][316][317][318].…”
Section: Resultsmentioning
confidence: 99%
“…More research is needed into the validity of the specific PDs listed in the AMPD, incorporating the specific impairment criteria [88••] and using mixture modeling to test whether they indeed represent latent categories [312]. Finally, future research should continue pursuing a comprehensive conceptualization of mental disorders that integrates major dimensions of personality and psychopathology [313][314][315][316][317][318].…”
Section: Resultsmentioning
confidence: 99%
“…The previous research on bi-factor models have used limited personality data (e.g., antisocial personality disorder) (Lahey et al 2012) and studied correlations between further personality traits and model-implied factors (Tackett et al 2013;Caspi et al 2014;Neumann et al 2016), but they did not study more comprehensive trait systems as a possible part of the factorial structure, as suggested by Oltmanns et al (2018). Here, we will do this and discuss the relative parsimony of the structures that the correlated-factor and bi-factor models suggest.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we investigated (i) the minimum number of underlying factors that are needed to adequately account for the population correlations between variables for 11 commonly studied psychiatric disorders, five pathological personality traits, and five normative personality traits, (ii) what these factors look like from correlated-factor versus bi-factor perspectives, and iiiwhat their heritability and genetic correlations are. We also (iv) address possible response style effects on factor structure, which have been frequently discussed in context of the p factor (e.g., Neumann et al 2016;Caspi & Moffitt 2018;Oltmanns et al 2018); namely, we controlled for extreme and acquiescent self-reporting styles (Weijters et al 2010a(Weijters et al , 2010bWetzel et al 2016) because they would have given rise to an apparent methods factor without obvious substantive interpretation. The personality research field has favored the dimensional trait systems because there has been little or no evidence supporting a typological organization of personality (Markon et al 2011;Haslam et al 2012;Rosenström & Jokela 2017), and the recently suggested DSM pathological personality trait system appears to capture all the genetic and most of the environmental variance in the older typological system of personality disorders (Reichborn-Kjennerud et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…MMPI) can be found in Rushton and Irwing (2011). More recently, Oltmanns et al (2018) specifically investigated the relations between the p-factor, the GFP and a general factor of personality disorder (GPD). In two studies using self-report (study 1) and multimethod data (study 2), significant associations were found.…”
Section: Personality and Psychopathologymentioning
confidence: 99%
“…Nevertheless, given the inverse relation of the GFP and p-factor derived from questionnaire-based studies e.g. (Oltmanns et al, 2018), this would logically follow that higher GFP scores should be associated with greater cerebellar volume. This hypothesis would need to be confirmed in future large scale studies.…”
Section: Part 3: Synthesismentioning
confidence: 99%